Reactive Power Compensation : a Practical Guide. - Hofmann, Wolfgang (John Wiley & Sons, 2012)
The comprehensive resource on reactive power compensation, presenting the design, application and operation of reactive power equipment and installationsThe area of reactive power compensation is gaining increasing importance worldwide. If suitably designed, it is capable of improving voltage quality significantly, meaning that losses in equipment and power systems are reduced, the permissible loading of equipment can be increased, and the over-all stability of system operation improved. Ultimately, energy use and CO2 emisson are reduced. This unique guide discusses the effects of reactive powe.